Fundamentals and principles of youth football in Iceland : the coaches’ perspectives - Elías Hlynur Lárusson 1998- (2023)
Fundamentals and Principles of Youth Football in Iceland The Coaches’ Perspectives Objectives: This study explores fundamentals and principles of youth football in Iceland. The rationale is to reveal how these aspects are perceived and whether they are visible in practice. This study is the first Icelandic study which focuses on this area of youth football. Methods: The study is qualitative in nature and is performed within phenomenology. In-depth qualitative interviews with six head youth coaches were conducted. The data analysis was informed by hermeneutic phenomenology where the emphasis is on descriptive and interpretative approach. The SWOT analysis was used where data were grouped into four categories (Strengths, Weaknesses, Opportunities and Threats). Results: The fundamentals and principles of youth football were multidimensional in nature. Several themes were identified such as the policy and structure of youth football which were considered both being a strength and a weakness. Participation sports/sports for all, human resources and positive culture were considered as strengths. Weaknesses were tension between participation sports and performance sports and a challenging work environment. Coaching philosophy, policy development, implementation, and follow-up and communication were perceived as opportunities. Financial worries, lack of facilities and equipment, organisational challenges and human mindset were considered a threat. Conclusion: The fundamentals and principles of youth football in Iceland have been affected enormously by the policy of participation sports/sports for all. This aspect has become a part of the positive cultural environment more than other items in existing clubs’ policies or guidelines. However, a tension was revealed between participation sports/sports for all and elite performance sports. Keywords: Youth football, fundamentals of youth football, policies and structure of youth football, youth football coaching, head youth coaches, soccer. Megináherslur í ...